Managing Value Propositions in Service Ecosystems - Boha, Julian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Julian Boha explores value propositions in ecosystems as they play an important role in communicating how a company aims to provide value to business partners and customers. Value propositions are used in our everyday language, yet the concept remains ambiguous as there is a lack of empirical evidence about value propositions and their formal development process. The author provides a much-needed understanding of value propositions within the context of ecosystems and offers tools to systematically create value propositions and orchestrate ecosystems to foster innovation. Further, this book advances to the current understanding of value propositions and their application in the context of innovative ecosystems. <br
Keywords: Innovation Ecosystems; Case Study Research; Value Propositions; Perceived Value Propositions; Ecosystem Orchestration; Management Practices; Managing Value Propositions; Service Ecosystems; Evolution of value propositions; Orchestrating service ecosystems; Management framework for service ecosystems